Evaluasi Dan Analisis Pengelolaan Limbah Medis Padat Pada Fasilitas Kesehatan Tingkat Pertama Kota Padang - Rahma Nella; Fuji Astuti Febria; Mahdi Mahdi (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
Medical waste management procedures of health facilities such as the use of plastic bags that have not been in accordance with the type and characteristics of waste, the use of disinfection of medical waste containers that have been used, the lack of use of Personal Protective Equipment. In addition, the knowledge and attitude of medical waste management officers are still low such as the colour of plastic bags used, maximum storage of medical waste. This study used quantitative descriptive methods with a sample of 58 samples using the guttman scale and the likert scale with Multiple Regression analysis. For First Level Health Facilities (FKTP) most have carried out medical waste management in accordance with established regulations but there are some stages that are still low such as Temporary Shelter and Onsite Transportation. For knowledge (p = 0.031), attitude (p = 0.007) and perception of leadership support (p = 0.000) in medical waste management officers are still relatively low and the result of multiple regressions that knowledge, attitude and leadership support have a real effect on solid medical waste management. For FKTP as Health Centers and Clinics have carried out medical waste management by established standards but for the dentist practice is still low in the application of regulations regarding the management of solid medical waste.